Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jstrokecerebrovasdis.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Prediction Score for Developing a Hospital-Acquired Infection after Acute Ischemic Stroke

Abstract: Background Hospital-acquired infections are a major cause of morbidity and mortality in acute ischemic stroke patients. While prior scoring systems have been developed to predict pneumonia in ischemic stroke patients, these scores were not designed to predict other infections. We sought to develop a simple scoring system for any hospital-acquired infection. Methods Patients admitted to our stroke center (07/08-06/12) were retrospectively assessed. Patients were excluded if they had an in-hospital stroke, unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
(42 reference statements)
1
34
0
2
Order By: Relevance
“…This indicates that the severity of neurological deficits is closely related to the use of antibiotics: the loss of swallowing function 26 , hypostatic pneumonia caused by impairment of physical activity, and aspiration or reflux caused by disturbance of consciousness 27 may lead to infection, in turn www.nature.com/scientificreports www.nature.com/scientificreports/ increasing PAUD. Our findings support previous results linking NIHSS score to the developed infection of patients with stroke 28 , which may help explain the observed association between high PAUD and in-hospital mortality. However, we did not observe an association of hematoma volume or GCS score with PAUD, although both factors are closely related to the occurrence of SAI after intracerebral hemorrhage [29][30][31] .…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that the severity of neurological deficits is closely related to the use of antibiotics: the loss of swallowing function 26 , hypostatic pneumonia caused by impairment of physical activity, and aspiration or reflux caused by disturbance of consciousness 27 may lead to infection, in turn www.nature.com/scientificreports www.nature.com/scientificreports/ increasing PAUD. Our findings support previous results linking NIHSS score to the developed infection of patients with stroke 28 , which may help explain the observed association between high PAUD and in-hospital mortality. However, we did not observe an association of hematoma volume or GCS score with PAUD, although both factors are closely related to the occurrence of SAI after intracerebral hemorrhage [29][30][31] .…”
Section: Discussionsupporting
confidence: 92%
“…One prior retrospective study reviewed 568 admissions for AIS to develop a scoring system to predict the likelihood of post-stroke infection. They identified age, diabetes, and stroke severity as predictors of infection, while sex was not found to be predictive of this outcome (8). Rodent studies have shown sexual dimorphisms in functional outcomes and inflammatory response after experimental brain ischemia suggesting that post-stroke infectious complications may also be sex dependent (9).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of infection in patients with acute stroke has been the subject of numerous clinical studies. Owing to different designs, patient selection criteria, diagnostic criteria, timing of assessment, and duration of follow-up, the results vary considerably, with a reported incidence of infection up to 90 % [9][10][11][12][13]. Almost all studies described pneumonia as the most frequent type of infection after stroke, followed by urinary tract infection [6].…”
Section: Rationale Behind Prophylactic Antibiotic Therapy In Strokementioning
confidence: 99%